Studies on mutagenic effect of phosphemide in barley - N. V. Tetyannikov; N. A. Bome (Труды по прикладной ботанике, генетике и селекции)
Background. The method of induced mutagenesis is used to temporarily increase the frequency of mutations, allowing a higher probability of obtaining plants with new alleles and traits valuable for breeding. The search for new agents with high mutagenic activity is of particular interest for the development of mutational breeding. A new mutagen for barley is phosphemide.Materials and methods. Field and laboratory studies were conducted in 2016–2018. Three barley genotypes were treated with an aqueous solution of phosphemide at two concentrations: 0.002% and 0.01%, exposure: 3 hours. Experimental data were statistically processed by the analysis of variance (ANOVA) using Statistica 7. The error of the mean (Sx) was calculated for the mean values. Significance of differences (P < 0.05) was determined by Student’s t-test. Mutation frequency (Mf), mutagenic effectiveness (ME), and efficiency (Me) were assessed.Results and conclusion. It was found that the greatest contribution to formation of field seed germination of mutant populations in M1 and M2 generations was made by the mutagenic factor (20,36%) and interaction of the genotype × environment (18,55%) and mutagen × environment factors (14,93%). The concentration of 0.01% was recognized as semi-lethal for two accessions. In the M2 generation, the mutagenic effectiveness of the 0.002% phosphemide concentration exceeded that of 0.01% more than 4 times. The low concentration was more effective for cv. ‘Zernogradsky 813’ (17.43%) and accession Dz02- 129 (12.04%). For C.I. 10995, a higher concentration of phosphemide had greater effect (29.66%) providing a high mutation frequency (9.79%) against a relatively low lethality (33.00%). Nine different types were identified in the mutation spectrum. In M3 generation, distinct inheritance of the changes was confirmed in 46.43% of families. The highest number of families with confirmed changes was recorded for C.I. 10995 in the experiment with a higher concentration.